Perspective of delayed Hypersensitivity: A review - Nnodim Johnkennedy; Njoku-Obi Treasure; Bako Hauwa (Newinera Publisher, 2022)
T cells enter tissues and are activated by antigen-presenting cells to produce cytokines that cause inflammation in the local area. In allergic contact dermatitis, drug eruptions, asthma, and autoimmune disorders, CD8+ T lymphocytes mediate DTH reactions. As an example of this type IV hypersensitivity, chronic DTH reactions, contact hypersensitivity, and hypersensitivity pneumonitis are all examples. Infiltration of an antigen-exposed region by Th1 cells and macrophages, which inflict tissue damage, is the primary cause of the delayed onset of symptoms. It has thus been outlined that this delayed hypersensitivity reaction.